Effects of the Duration of Wheat and Maize Straw Returning on Rill Erosion Resistance in Brown Soil in the Earth-rocky Mountainous Area of Northern China - ZHANG Hanyu; LI Jiaqian; ZHAO Yajie; LI Jingjiang; LIU Zhihua; FANG Nufang; LIU Qianjin (Shuitu Baochi Xuebao)
［Objective］ Research on the effects of the duration of straw returning on rill erosion resistance can provide scientific evidence for rill erosion modeling and controlling in sloping farmland. ［Methods］ Taking straw returning durations of 0 years (CK), 3—4 years (R1), 5—6 years (R2), 7—8 years (R3), 9—10 years (R4), 15 years (R5), and 20 years (R6) as the study subjects, soil samples were collected and analyzed. Partial least squares regression analysis was applied to identify the main controlling factors of soil erosion resistance under straw returning conditions. ［Results］ 1) With the increase of straw returning duration, rill erodibility (Kd) first decreased, then increased, and decreased again. The Kd values of R2, R3, R5, and R6 were significantly lower than that of CK [170.38 cm3/(N·s)]. With the increase in the duration of straw returning, soil critical shear stress (τc) showed a trend of first increasing and then decreasing, with the pattern of R1=R3>R2>CK>R4>R6>R5, although the differences among treatments were not significant. 2) Compared to CK, all straw returning treatments reduced soil bulk density (BD), the content of water-stable aggregates >0.25 mm (WG0.25), and exchangeable sodium ions, while increasing total porosity and soil saturated moisture content (SWC), although the effects on soil properties varied across treatments. 3) Among all the main controlling factors of Kd, Kd decreased with the increases in exchangeable magnesium ions, soil organic matter, humic substances, fulvic acid (FA), humin, and exchangeable calcium ions, but increased with the increase in WG0.25. Among all the main controlling factors of τc, τc was positively correlated with FA, dry-sieved aggregates >0.25 mm, and BD, and negatively correlated with soil moisture content and SWC. ［Conclusion］ Straw returning for 5—8 years or 15—20 years significantly reduced Kd, helped to improve soil erosion resistance and can effectively control rill erosion.